Champions during Crises Scenarios: High Growth and Persistent High Growth Firms - Mariasole Bannò; Celeste Amorim Varum (Research in Applied Economics, 2024)
Our paper aims to participate to the growing policy discussion on high-growth firms (HGFs) by analyzing persistence of high growth patterns over crisis. During downturn periods, such as post pandemic one, policy makers seek sources to maintain competitiveness and accelerate growth. Being dynamic players in economic growth and job creation, persistent high-growth firms are notable candidates for assuming that role under such circumstances. Therefore, in this study we explore the determinants and characteristics of HGFs and persistent high-growth firms (PHGF) in a crisis scenario. We use a sample of 190,247 firms from 2007 to 2014. We estimate a multinomial probit model with independent idiosyncratic components across the different categories (i.e. HGFs, PHGFs and other firms) using full maximum likelihood. In a second phase we explore which characteristics of HGFs affect the probability of being a PHGFs. HGFs are characterized by higher productivity and leverage, and PHGFs systematically differ from other HGFs only in what regards degree of international involvement. HGFs probability of maintaining high growth rates is very low. HGFs are essentially one-hit wonders and it is debatable whether policymakers can enhance economic results by targeting them. Policy makers should be directed towards those firms which have in principal the potential to be winners, but only through policy intervention these aided firms can realize their great potential (i.e. pick and build winner).